The ground potential rise effect reduction on sensitive electronic equipment - Arwut Puttarach (2018)
This paper presents a reduction of ground potential rise effect on sensitive electronic equipment in medium voltage distribution substation. The study, supported by Provincial Electricity Authority (PEA), Thailand, is based on ground grid systems analysis on Royal Flora RATCHAPHRUEK distribution Substation. The research procedures of study are soil resistivity analysis and ground grid design characteristics by using CDEGS program. The supporting soil resistivity data have been obtained from actual field test at the substation. The result has shown that soil resistivity was interpreted to two-layer earth structure. In new ground grid design studies, ground potential rise (GPR) along the sensitive electronic equipment area was lessened. Moreover, touch voltage and step voltage of the substation were also significantly reduced more than the unprotected area.